Measuring the Quality of the Home Environment of Young Children in Uruguay: Socioeconomic Gradients in the Home Inventory - Florencia López Bóo; Mayaris Cubides Mateus; Rita Sorio; Giorgina Garibotto; Christian Berón (Institute of Labor Economics (IZA), 2019)
Uruguay is one of very few countries in Latin America that has a nationally representative, longitudinal survey of early childhood development. In 2015–2016, during the second wave of the survey, an observational module on the home environment was administered at scale for the first time. The module included items from two subscales (responsiveness and acceptance) of a widely used instrument that measures the quality of the physical and emotional environment: the HOME inventory. We find that the set of items administered from the HOME has very good concurrent validity with child development and maternal personality traits, as well as with other relevant socioeconomic variables. In line with the literature, our analysis shows that children from the most vulnerable families are exposed to a lower-quality home environment—that is, less responsive and more punitive. Interestingly, Uruguayan children are exposed to better environments as compared to children in predominantly rural samples from the Latin America and Caribbean region; however, they present comparable environments when compared to similar samples from countries such as Brazil and Chile.
Keywords: I10; I30; J13; I38; 330; child development; parenting practices; home; quality of the home environment; Uruguay; ASQ; ENDIS